Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 2 - Derivatives - 2.3 Differentiation Formulas - 2.3 Exercises: 8

Answer

$H'(u) = 6u+5$

Work Step by Step

$H(u) = (3u-1)(u+2)$ Product Rule $H'(u) = (3u-1)(1) + (3)(u + 2)$ Simplify $H'(u) = 3u-1+3u+6$ Simplify $H'(u) = 6u+5$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.